Core level photoionization on free sub-10-nm nanoparticles using synchrotron radiation - Meinen, Jan; Khasminskaya, Svetlana; Eritt, Markus; Leisner, Thomas; Antonsson, Egill; Langer, Burkhard; Rühl, Eckart (Review of scientific instruments, 2010)
A novel instrument is presented, which permits studies on singly charged free nanoparticles in the diameter range from 1 to 30 nm using synchrotron radiation in the soft x-ray regime. It consists of a high pressure nanoparticle source, a high efficiency nanoparticle beam inlet, and an electron time-of-flight spectrometer suitable for probing surface and bulk properties of free, levitated nanoparticles. We show results from x-ray photoelectron spectroscopy study near the - Si  - L - 3,2 - Si L3,2 - -edge on 8.2 nm - SiO - 2 - SiO2 - particles prepared in a nanoparticle beam. The possible use of this apparatus regarding chemical reactions on the surface of nanometer-sized particles is highlighted. This approach has the potential to be exploited for process studies on heterogeneous atmospheric chemistry.